Democratic authority and the separation of church and state - Audi, Robert, 1941- (New York ; Oxford : Oxford University Press, 2011)
This text clarifies the relation between religion and ethics articulates principles governing religion in politics, and outlines a theory of civic virtue. It frames institutional principles to guide governmental policies toward religion and counterpart standards to guide individual citizens.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Democracy -- Religious aspects; Religion and state